Transcriptional Studies on Trypanosoma cruzi – Host Cell Interactions: A Complex Puzzle of Variables - Libisch, María Gabriela; Rego, Natalia; Robello, Carlos (Frontiers in Cellular and Infection Microbiology, 2021)
Chagas Disease, caused by the protozoan parasite Trypanosoma cruzi, affects nearly eight million people in the world. T. cruzi is a complex taxon represented by different strains with particular characteristics, and it has the ability to infect and interact with almost any nucleated cell. The T. cruzi-host cell interactions will trigger molecular signaling cascades in the host cell that will depend on the particular cell type and T. cruzi strain, and also on many different experimental variables. In this review we collect data from multiple transcriptomic and functional studies performed in different infection models, in order to highlight key differences between works that in our opinion should be addressed when comparing and discussing results. In particular, we focus on changes in the respiratory chain and oxidative phosphorylation of host cells in response to infection, which depends on the experimental model of T. cruzi infection. Finally, we also discuss host cell responses which reiterates independently of the strain, cell type and experimental conditions.